Inside Mystery Of A Tumor In The Stomach Of A Young Female - DR.ANIL FONSECA,; DR.DAPHNE FONSECA, (International Journal of Pharma and Bio Sciences, 2012)
Gastrointestinal Stromal Tumours are the commonest mesenchymal tumors of the gastrointestinal tract, the stomach and small intestine being the favored sites. They rarely occur in the colon and rectum and esophagus. The diagnosis is difficult, especially when there are no pathognomic features to suggest GIST on preoperative clinical examination and investigations, and only a detailed histopathological analysis of the specimen reveals their true nature. Here, we report a case of a young female patient who presented with vague abdominal pain which was diagnosed histopathologically as GIST of the stomach..